2016
DOI: 10.1177/1478210316674159
|View full text |Cite
|
Sign up to set email alerts
|

How does private tutoring mediate the effects of socio-economic status on mathematics performance? Evidence from Turkey

Abstract: Private tutoring refers to additional instruction out of school. With its determinants and effects, private tutoring has received increasing attention from scholars over the past decades. Because of the increasing role of school and high-stakes exams, the demand for private tutoring has increased tremendously in Turkey. The purpose of this study is to examine whether private tutoring mediates the effects of socio-economic status (SES) on students’ mathematics performance in the country. This study also address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Perhaps Turkish parents press for greater math performance at earlier ages than American parents. For example, the literature has reported that it is not uncommon for Turkish parents to hire tutors to improve their child's performance in elementary school years (Atalmis, Yilmaz, & Saatcioglu, 2016). In the Turkish culture, extra rigor goes into selecting math and science teachers, and parents also know that preparation is a joint effort between these teachers and parents to ensure college entry for their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps Turkish parents press for greater math performance at earlier ages than American parents. For example, the literature has reported that it is not uncommon for Turkish parents to hire tutors to improve their child's performance in elementary school years (Atalmis, Yilmaz, & Saatcioglu, 2016). In the Turkish culture, extra rigor goes into selecting math and science teachers, and parents also know that preparation is a joint effort between these teachers and parents to ensure college entry for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Among these three reasons, the most probable explanation for the results obtained is the first one because Turkish students, based upon test scores, are tracked into college and non-college pathways far earlier than American students. Atalmis, Yilmaz, and Saatcioglu (2016)…”
Section: Discussionmentioning
confidence: 99%
“…Many shadow education studies include both parental income and educational level as indicators of SES, which are known to be correlated (Entrich & Lauterbach, 2019). Some studies examine SES as a main determinant of shadow education usage (e.g., Southgate, 2009), whereas others assess the effect of SES on shadow education usage while controlling for other student-level variables (Atalmis et al, 2016;Buchmann et al, 2010;Guill & Bos, 2014;Lee, 2007). Both strands of research report a positive relationship between SES and the use of shadow education.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although students with varying socioeconomic backgrounds may engage in some form of tutoring, Buchmann et al (2010) suggest that students from advantaged families buy into more intensive -i.e., more expensive -forms of shadow education to stay ahead of the competition for admission to universities. Thus, the type of shadow education students participate in appears to relate to their SES (Atalmis et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation